Implementasi untuk Prediksi Jumlah Kedatangan Wisatawan Domestik Pulau Bali menggunakan Algoritme Performance Improved Holt winters - Nabila Arief; Mochammad Tanzil Furqon; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The arrival of tourists into a tourist destination (DTW) has brought prosperity and to local people. Therefore, it is a sector that governments rely on in Indonesia to generate foreign exchange reserves. According to a study conducted by the World Travel and Tourism Council (WTTC) in 2004, the tourism sector can increase local income because of its Quick Yielding Industry. But the number of visitors entering an area is uncertain, for it was predicted the arrival of the tourists. In the study his method was Performance Improved Holt winters so it could be obtained information regarding predictions of the number of domestic tourists arriving to Bali. Performance Improved Holt winters was used for tourist predictions to Bali because of Improved methods used to predict seasonal data patterns. Performance Improved Holt winters rely on scaling trends and seasonal improvements based on the smoothing level equations, the smoothing trend and the smoothing seasonal equations, using data of the number of domestic tourists to Bali during January 2004-December 2018 received from bali.bps.go.id (official website of the BPS). Based on the tests done on this research, the value parameter Î± (alpha) = 0,03; Î² (beta) = 0,003; Î³ (gamma) = 0,04 and value of the smallest error using MAPE is 8% with the number of training data = 168 and testing data = 12.